MORPHOLOGY AND SYSTEMATION POSITION OF O CERVIPEDIS - CABALLERO Y CABALLERO, EDUARDO (Instituto de Salubridad Publica y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1977)
Fifth of a series of reviews of virus diseases This number deals with the, mechanism of transmission and agents of infection Portals of entrance to the body are classified such as the intact skin, the gastro-enteric canal, the respiratory epithelia, the
ANN MAG NAT HIST, LONDON
Keywords: MORPHOLOGY, SYSTEMATION POSITION, O CERVIPEDIS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL